Simultaneous load management strategy for electronic manufacturing facilities by using epso algorithm / M.F. Sulaima ... [et al.] - Sulaima, M.F; Dahlan, N.Y; Bohari,, Z.H; Nasir, M.N.M; Mustafa, R.F; Duc, Luong Nguyen (Universiti Teknologi MARA, 2021)
Increased power demand has contributed to the power generation tension. Thus, there were critical needs for a better Price Based Program (PBP) policy for the consumers. In Peninsular Malaysia, through the development of a policy for the regulated market plan, the Enhanced Time of Use (ETOU) tariff was introduced by the utility to promote better price signals to the industrial consumers who contribute to the most massive energy consumption every year. However, fewer industrial consumers join the program due to a lack of Load Management (LM) knowledge while not confident in the price rate signal compared to the previous tariffs. Due to that reason, this study proposed simultaneous LM strategies for the selected power consumption profile in the electronic manufacturing facilities. Meanwhile, the Evolutionary Particle Swarm Optimization (EPSO) was adopted to search for the upright power consumption profiles of those average 11 locations of the manufacturing. The analysis of the results has compared to the baseline existing flat and Time of Use (TOU) tariffs. The results show an improvement in the energy consumption and maximum demand costs reduction of ~14-16% when load management was applied correctly. It is hoped that this study's results could help companies' management of developing a strategic plan for the successful load management program.